DEVELOPMENT OF INTERACTIVE BLOSPOT LEARNING MEDIA USING A DIGITAL LITERACY APPROACH AT MIN 4 JOMBANG - Kholifah, Nur; Rofi'ah, Siti (Jurnal Gentala Pendidikan Dasar, 2026)
This study was motivated by the limited availablity of learning media capable of concretely visualizing IPAS material, causing students to struggle with understanding abstract concepts. The study aims to develop an interactive blogspot learning medium using a digital literacy approach and to determine its suitability as an IPAS learning medium at MIN 4 Jombang. This study employed the research and development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation and evaluation. The results indicate that the learning medium received a validation parcentage of 90% from media experts, 92% form content experts and 100% form  instructional experts, with an average suitability rating of 94%, falling into the “highly suitable” category. The small grup pilot test yielded a 90% success rate, while the large grup pilot test yielded an 88,26% success rate, both falling into the “highly suitable” category. Based on these results, the interactive blogspot learning media with a digital literacy approach is deemed highly suitable for use as an IPAS learning medium at MIN 4 Jombang